Elementary differential equations and boundary value problems / William E Boyce, Richard C DiPrima - Boyce, William E
Written primarily for undergraduate students of mathematics, science, or engineering, who typically take a course on differential equations during their first or second year. The main prerequisite is a working knowledge of calculus. The environment in which instructors teach, and students learn differential equations has changed enormously in the past few years and continues to evolve at a rapid pace. Computing equipment of some kind, whether a graphing calculator, a notebook computer, or a desktop workstation is available to most students. The seventh edition of this classic text reflects this changing environment, while at the same time, it maintains its great strengths - a contemporary approach, flexible chapter construction, clear exposition, and outstanding problems. In addition many new problems have been added and a reorganisation of the material makes the concepts even clearer and more comprehensible. Like its predecessors, this edition is written from the viewpoint of the applied mathematician, focusing both on the theory and the practical applications of differential equations as they apply to engineering and the sciences.